Return on Assets, Current Ratio, Debt to Equity Ratio, and Investment Decisions Affect the Value of Tourism, Hotel, and Restaurant Companies - Kholif Matunni’ Mah; Herry Krisnandi; Kumba Digdowiseiso (Jurnal Syntax Admiration, 2023)
Return on Assets (ROA), Current Ratio (CR), Debt to Equity Ratio (DER), and Capital Expenditure to Book Value of Assets (CAPBVA) Investment Decision on Company Value (Tobin's Q) is the purpose of this study. Using the annual financial statements of 35 companies in the Tourism, Hotel, and Restaurant subsector listed on the Indonesia Stock Exchange (IDX) for the five-year period 2017-2021, this study uses secondary data. Purposive sampling is used for sampling. The panel data regression analysis used in this study was processed using the Eviews 10 program system for data analysis. The results of this research test Return on Assets (ROA) and Debt to Equity Ratio (DER) have a positive and significant effect on Company Value (Tobin's Q), while Capital Expenditure to Book Value of Assets (CAPBVA) investment decisions have a negative and significant effect on Company Value (Tobin's Q) and Current Ratio (CR) have no effect on Company Value (Tobin's Q).